Solvent-Induced Supramolecular Assembly of a Peptide-Tetrathiophene-Peptide Conjugate - Guo, Zongxia; Wang, Yujiao; Zhang, Xiao; Gong, Ruiying; Mu, Youbing; Wan, Xiaobo (Frontiers in Chemistry, 2019)
The assembly of a peptide-tetrathiophene-peptide (PTP) conjugate has been investigated in mixed solvents, which has different polarities by changing the solvent proportions. It was found that PTP can form fibers in THF/hexane solutions with 40-80%v of hexane. The fibers were stable and did not change on time. On the other hand, PTP formed ordered structures in a mixed solution with the water content from 40 to 60%v. For the as-prepared solutions, two nanostructures vesicles and parallelogram sheets were obtained. The parallelogram sheets could transform into vesicles on time. The fibers showed supramolecular chirality, however, there is no cotton effect for vesicles and parallelogram sheets. UV-vis, FL, XRD, FT-IR, and CD spectra together with SEM, AFM, TEM were used to characterize the nanostructures and properties of the assemblies. Molecular packing mechanism was proposed based on the experimental data.